Knowledge synthesis in software industries: a survey in Sri Lanka. Issue 3 (1st August 2017) - Vasanthapriyan, Shanmuganathan; Xiang, Jianwen; Tian, Jing; Xiong, Shengwu
Abstract: Software development is a knowledge intensive and a collaborative activity, which mainly depends on knowledge and experience of the software developers. Knowledge management in software industries aims to create an environment for continuous knowledge sharing and creation to remain competitive. This study investigates the current status of knowledge management in three software industries in Sri Lanka on the basis that they claimed to apply knowledge management practices within their organizations using both quantitative and qualitative methods. The knowledge synthesis theory is used in this study to synthesize a variety of knowledge, unseen problems, obstructions, and the corresponding underlying reasons in implementing the knowledge management practices. Findings of this study emphasized that while knowledge management practices were considered to be important, organizational learning and culture, attitudes and behaviors of employees, information technology infrastructure, and rewards systems were inadequate to address an effective management of knowledge in these three software industries. One of the findings showed that, software developers believe both software engineering knowledge and information communication technology are considered to be an enterprise's strategic asset and a main source to create competitive advantage. Findings also presented a compelling evidence of the soundness for the need of knowledge management practices to manage software engineering knowledge.